Catalase in Leishmaniinae: With me or against me - Kraeva, Natalya; Horáková, Eva; Kostygov, Alexei Y; Kořený, Luděk; Butenko, Anzhelika; Yurchenko, Vyacheslav; Lukeš, Julius (Infection, genetics and evolution, 2017)
The catalase gene is a virtually ubiquitous component of the eukaryotic genomes. It is also present in the monoxenous (i.e. parasitizing solely insects) trypanosomatids of the subfamily Leishmaniinae, which have acquired the enzyme by horizontal gene transfer from a bacterium. However, as shown here, the catalase gene was secondarily lost from the genomes of all Leishmania sequenced so far. Due to the potentially key regulatory role of hydrogen peroxide in the inter-stagial transformation of Leishmania spp., this loss seems to be a necessary prerequisite for the emergence of a complex life cycle of these important human pathogens. Hence, in this group of protists, the advantages of keeping catalase were uniquely outweighed by its disadvantages.
Keywords: signální transdukce; Animals; houby; Host-Parasite Interactions; Humans; katalasa; Psychodidae; delece genu; Trypanosomatina; genom; lidé; zvířata; peroxid vodíku; Gene Deletion; Life Cycle Stages; Fungi; Signal Transduction; Gene Expression; interakce hostitele a parazita; Leishmania; Phylogeny; fylogeneze; Catalase; Hydrogen Peroxide; exprese genu; stadia vývoje; Bacteria; Genome